EVALUATION OF ANAPHYLAXIS KNOWLEDGE LEVELS IN 4TH AND 5TH YEAR STUDENTS OF FACULTY OF DENTISTRY - Salih Düzgün; Mehmet Doğan; Emre Bulbul (Current Research in Dental Sciences, 2025)
Objective: Anaphylaxis is a rapidly developing and life-threatening phenomenon. Rare cases of anaphylaxis may occur during dental practice and may cause loss of life in patients. This study aimed to evaluate the level of anaphylaxis knowledge in 4th and 5th-year dental students.Methods: This descriptive and cross-sectional study was conducted on 4th and 5th-year students at Erciyes University Faculty of Dentistry between September 1 and 31, 2024.Results: In the research group, 50.7% of the students were in the 4th year, and 58.9% were female. While 47.8% of the students in the research group received first aid training, those who thought that they could fully manage anaphylaxis in case of anaphylaxis were higher in those who did not receive first aid training in terms of knowing which immunoglobulin plays a role in anaphylaxis (p0.05) for adrenaline, which is the first preferred drug in the treatment of anaphylaxis; IM, which is the first preferred route of drug administration; and 0.01 mg/kg; which is the drug dose (Table 2).Conclusions: The study's findings, which indicate a low rate of anaphylaxis in the study group, underscore the need for in-service first aid training for students in formal education and their professional lives after graduation. These results have practical implications for the professional lives of dental students, highlighting the importance of anaphylaxis management in dental care.